Concentrations of Cu and Pb in the offshore and intertidal sediments of the west coast of Peninsular Malaysia - Yap, C.K; Ismail, A; Tan, S.G; Omar, H (Elsevier, 2002)
Malaysia is now a developing country and on her way towards being an industrialised one by the year 2020. Most of her industries and urban areas are located on the west coast of Peninsular Malaysia. In addition, the offshore area of the west coast is now one of the busiest shipping lanes in the world. These two phenomena make the intertidal and offshore areas of the west coast of Peninsular Malaysia interesting for scientific studies. Therefore, this study focused on both the offshore and intertidal sediments of the west coast of Peninsular Malaysia. Sampling for sediment samples were done from the northern to the southern ends of the peninsula and these sediment samples were analysed for Cu and Pb. It was found that total Cu concentrations ranged from 0.25 to 13.8 and 0.40 to 315 μg/g dry weight (dw) for offshore and intertidal sediments, respectively. For Pb, it ranged from 3.59 to 25.4 and 0.96 to 69.8 μg/g dw for the offshore and intertidal sediments, respectively. The ranges of Cu and Pb found from the west coast of Peninsular Malaysia were low in comparison to regional data. However, some intertidal areas were identified as receiving anthropogenic Cu and Pb. Geochemical studies revealed that the ‘nonresistant’ fraction for Pb contributed about 70.0% to 75.0% and 54.0% of the total Pb concentration in the offshore and intertidal sediments, respectively. As for Cu, the ‘nonresistant’ fraction contributed about 46.2% to 60.4% and 46.3% of the total Cu concentration in the offshore and intertidal sediments, respectively. The ‘nonresistant’ fraction contained mostly of anthropogenic metals besides natural origins. These ‘nonresistant’ percentages indicated that both the offshore and intertidal areas could have received anthropogenic-derived metals, which could be influenced by physico-chemical properties of the sediments. Although the present data indicated that contamination due to Cu and Pb in the west coast of Peninsular Malaysia especially in the offshore areas were not serious, regular biomonitoring studies along the west coast of Peninsular Malaysia are recommended.